Lymphocytes Infiltration and Expression of PD-1 and PD-L1 in Colorectal Cancer Between HIV-Infected and Non-HIV-Infected Patients: A Propensity Score Matched Cohort Study - Cao, Ye; Wu, Qian; Lian, Shixian; Deng, Li (Frontiers in Oncology, 2022)
Background Tumor-infiltrating lymphocytes (TILs) and expression of programmed cell death 1 (PD-1)/programmed death ligand-1 (PD-L1) are crucial for antitumor immunity. However, the status remains undetermined in HIV-infected colorectal cancer (CRC), limiting the use of immunotherapy in HIV-infected CRC patients. Methods We examined 27 HIV-infected patients and 120 non-HIV-infected patients with CRC from 2015-2020 at Shanghai Public Health Clinical Center. After matching the propensity score, 13 paired patients in the two groups were also compared. The expression of PD-1/PD-L1 as well as tumor-infiltrating CD4, CD8, and CD56 immune cells was examined using multiplex immunofluorescent analysis. The cell density for positive staining was calculated (cells/mm2) and compared between HIV-infected and non-HIV-infected groups. In addition, the co-expression of PD-1 on immune cells and PD-L1 on tumor cells was compared in these two groups. Results The mean densities of tumor-infiltrating CD4, CD8, CD56 immune cells were 620.2, 261.2, and 0.2 cells/mm2, respectively, in HIV-infected colorectal tumors compared with 698.6, 243, and 14 cells/mm2 in non-HIV-infected tumors. PD-1 expression was 227 cells/mm2 in HIV-infected tumors and 365.2 cells/mm2 in non-HIV-infected tumors. Besides, PD-L1 expression was 108.5 cells/mm2 in HIV-infected tumors and 126.8 cells/mm2 in non-HIV-infected tumors, and no significant difference was found between the two groups. Similarly, there were no significant differences in the expression of PD-1 on TILs and PD-L1 on tumor cells. Conclusion HIV-infected CRC patients had similar tumor-infiltrating lymphocytes (CD4 and CD8 T cells) compared to non-HIV-infected controls and substantially similar PD-1 expression on TILs and PD-L1 expression on tumors. These results support the inclusion of HIV-infected CRC patients in future immunotherapy trials.